Analisis Daya Saing Komoditas Karet Indonesia ke Pasar Global - Puspita, Della Yoga; Nasir, Muhammad Safar (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
International trade is an important activity for a country to carry out. One of the reasons why Indonesia is active in international trade is because of its abundant natural resources and the variety of export commodities. Rubber is a crop that Indonesia relies on which contributes greatly to Indonesia's foreign exchange earnings. It is known that Indonesia is one of the countries with the highest level of rubber productivity in the world so that Indonesian natural rubber has potential and opportunities in international trade. Therefore, in this section an in-depth analysis will be carried out to analyze the competitiveness of Indonesia's HS 40 commodity exports in international markets using the Revealed Symmetric Comparative Advantage (RSCA) method. The data used was obtained from the United Nation Commodity Trade (UN Comtrade). Indonesia has a comparative advantage over the 3 main rubber export destination countries, namely the United States, Japan, China in 2019-2021. It is said to have a comparative advantage because the RSCA value is 0. Indonesia means that as national natural rubber production increases, the number of natural rubber exports will increase. Indonesia's natural rubber exports are significantly influenced by natural rubber production.